(untitled) (Advancements in Homeopathic Research, 2022)
Depression is a common psychosomatic disorder with persistent low mood, reduced energy, loss of interest and disturbance in activities of daily living. In this case report, a 52 year old male, known case of depression, taking antidepressant medicines, was treated using individualized homoeopathic medicine Arsenicum album selected on the basis of delusions. The study showed significant improvement according to Hamilton Depression Rating Scale. This study suggests that homoeopathy can be used in treatment ofpsychosomatic mood disorders effectively.